Outcome of Malnourished Children Admitted in the Nutritional Rehabilitation Home - Rauniyar, Lalan Prasad; Rouniyar, Maya; Jha, Rashmi; Yadav, Aman Kumar; Sah, Mukesh Kumar (Journal of Nepal Health Research Council, 2023)
Background: Globally, the burden of malnutrition, especially undernutrition, as well as the consequences of malnutrition is of the rise which is especially of significant concern for underdeveloped countries. Countries like Nepal are also facing a similar problem of malnutrition. In Madhesh province, among the under 5 children the incidence of chronic malnutrition is 29.3%. Our aim is to assess the malnourishment in the children of Madhesh province in Nepal. Methods: This cross-sectional quantitative study was carried out among 409 malnourished children who were admitted from July 17, 2018 to July 16, 2022 at NRH in Gajendra Narayan Singh Hospital. Collected data were fed into Microsoft-excel and analyzed using SPSS software, version-2016. As data were normally distributed, frequency, percentage, mean and standard deviation were calculated for descriptive analysis. To find out the association of categorical variables, the Chi-square test or Fisher’s Exact test was used where appropriate. P-value <0.05 was significant. Results: Out of 409 malnourished cases, 145 cases were SAM (SD<-3) and 264 cases were MAM (-2 to -3SD) at the time of admission. The mean increment in the weight was 1.14±0.44 kg. The average length of stay was 19.82±8.73 days. There is a significant difference (p<0.001) in the length of stay among the SAM and MAM cases of our study and a difference in the increment of weight in comparison to mean weight gain (1.14±0.44 kg) with respect to the length of stay of the malnourished child who stayed for more than 28 days and less. Conclusions: There is significant weight gain in malnourished children after management at the Nutritional Rehabilitation Center. Keywords: Height; increment in weight; malnourished child; moderate acute malnutrition; nutritional rehabilitation home